Perbandingan Pengaruh Terapi Musik Mozart dan Terapi Tertawa Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi di Panti Sosial Lanjut Usia Harapan Kita Palembang: Penelitian - Yora Nopriani; Rahmawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
According to WHO, approximately 1.28 billion adults aged 30–79 years in the world suffer from hypertension which is the leading cause of premature death. Treatment includes pharmacological and non-pharmacological therapies, such as classical music and laughter therapy. This study aims to compare the effects of Mozart music therapy and laughter therapy on reducing blood pressure in hypertensive elderly at Harapan Kita Palembang Social Home for the Elderly in 2025. The method used was a quasi-experimental with a two-group pretest–posttest control design, involving the entire population of hypertensive patients totaling 30 respondents in March–April 2025. The results showed that the average systolic blood pressure decreased from 161.93 mmHg to 140.4 mmHg after Mozart music therapy, and from 162.53 mmHg to 146.53 mmHg after laughter therapy. Both had a significant effect on reducing blood pressure with p = 0.012 (systolic) and p = 0.023 (diastolic).